2016
DOI: 10.4209/aaqr.2015.05.0358
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Measurements at South Pole: Climatology and Impact of Local Contamination

Abstract: The Atmospheric Research Observatory (ARO), part of the National Science Foundation's (NSF's) Amundsen-Scott South Pole Station, is located at one of the cleanest and most remote sites on earth. NOAA has been making atmospheric baseline measurements at South Pole since the mid-1970's. The pristine conditions and high elevation make the South Pole a desirable location for many types of research projects and since the early 2000's there have been multiple construction projects to accommodate both a major station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
7
15
0
Order By: Relevance
“…The daily mean average of 53 (±55) ng m −3 is in accordance with previous observations in remote locations of the world shown in Table 1 (Bodhaine, 1995;Andreae et al, 1995;Derwent et al, 2001;von Schneidemesser et al, 2009;Marinoni et al, 2010;Sheridan et al, 2016). Andreae et al (1995) found eBC mass concentrations lower than 50 ng m −3 along a cruise transect at 19 • S over the south-east Atlantic between Brazil and Angola, except when approaching the African continent, when concentrations increased in the range 50-150 ng m −3 , indicating a strong continental influence in this otherwise pristine environment.…”
Section: Temporal Variability In Ebc Concentrationssupporting
confidence: 90%
“…The daily mean average of 53 (±55) ng m −3 is in accordance with previous observations in remote locations of the world shown in Table 1 (Bodhaine, 1995;Andreae et al, 1995;Derwent et al, 2001;von Schneidemesser et al, 2009;Marinoni et al, 2010;Sheridan et al, 2016). Andreae et al (1995) found eBC mass concentrations lower than 50 ng m −3 along a cruise transect at 19 • S over the south-east Atlantic between Brazil and Angola, except when approaching the African continent, when concentrations increased in the range 50-150 ng m −3 , indicating a strong continental influence in this otherwise pristine environment.…”
Section: Temporal Variability In Ebc Concentrationssupporting
confidence: 90%
“…Observations of equivalent black carbon (eBC) have been collected by aethalometers deployed at the Halley Station located on the Brunt Ice Shelf in the Weddell Sea (Wolff & Cachier, 1998), on the Antarctic Peninsula (Pereira et al, 2006), at Neumayer Station on the Eefkström Ice Shelf in the Northeast Weddell Sea (Weller et al, 2013), at McMurdo Station (Hansen et al, 2001), and over several decades at the South Pole Station (Bodhaine, 1995;Hansen et al, 1988;Sheridan et al, 2016;Warren & Clarke, 1990). In general, these studies found that eBC is present on the continent at low concentration (0.3-8.3 ng/m 3 , Table 1) at their respective locations, with the exception of higher concentrations around field camps (~20 to~300 ng/m 3 at McMurdo Station, Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…After corrections, absorption coefficients measured by the PSAP or CLAP have an uncertainty of ∼ 20 % (Sherman et al, 2015). Finally, all data are passed through a qualityassurance-quality-control editing process in which measurement records are screened for atypical aerosol parameters (see Delene andOgren, 2002, andSheridan et al, 2016, for detailed descriptions of quality assurance and quality control procedures). Points that appear anomalous due to local pollution sources (nonrepresentative of regional aerosol), instrument error or excessive noise are not included in this analysis.…”
Section: Data and Instrumentsmentioning
confidence: 99%